Targeting Orphan Nuclear Receptors NR4As for Energy Homeostasis and Diabetes - Zhang, Chenyang; Zhang, Bin; Zhang, Xuelian; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2020)
Orphan nuclear receptors are important members of the nuclear receptor family and may regulate cell proliferation, metabolism, differentiation and apoptosis. NR4As, a subfamily of orphan nuclear receptors, have been reported to play key roles in carbohydrate and lipid metabolism and energy homeostasis. Popularity of obesity has brought a series of metabolic diseases such as diabetes and its complications. While imbalance of energy intake and expenditure is the main cause of obesity, the concrete mechanism has not been fully understood. It has been reported that NR4As have significant regulatory effect on energy homeostasis and diabetes, and were expected to become new targets for discovering drugs for metabolic syndrome. There were already a number of researches demonstrated that abnormality of metabolism induced by changed NR4As levels may contribute to numerous diseases, such as chronic inflammation, tumorigenesis, diabetes and its complications, atherosclerosis and other cardiovascular diseases. However, systematic reviews concentrated on the roles of NR4As in mediating energy homeostasis and diabetes remains limited. Therefore, this article introduced structure and regulation of NR4As, their critical function in energy homeostasis and diabetes, as well as chemicals that may regulate them. Our work aimed to provide valuable evidence for the research and development of drugs on obesity and related metabolic diseases targeting NR4A.